Temperature Measurement by Optical Emission Spectroscopy of the Plasma Jet Produced by a High Velocity Plasma Spray (HVPS) - Ridenti, Marco A.; Reis, Joares; Caliari, Felipe; Miranda, Felipe; Essiptchouk, Alexei [UNESP]; Filho, Gilberto Petraconi (Institute of Electrical and Electronics Engineers (IEEE), 2024)
In this work, we report the results from an optical emission spectroscopy experiment designed to investigate the molecular emissions from a plasma jet produced by a high velocity plasma spray (HVPS). By fitting the spectra, we were able to infer the rotational temperature of the electronic excited molecules OH (A2Σ +), CN (B2\Σ +), N2 (C2\Πu), and N 2+ (B2\Σ +u). We verified that rotational distributions were consistent with the local thermodynamic equilibrium hypothesis. However, the vibrational distribution of the excited species CN (B2Σ+) was overpopulated with respect to the expected equilibrium distribution. We proposed a model to describe this distribution, which provided good fittings. Lastly, we computed the energy balance equations of the sprayed particles with simplifying assumptions with the goal of getting some physical insight on the energy exchange dynamics between the plasma and the particles.
Keywords: Molecular spectroscopy; nonequilibrium plasmas; optical emission spectroscopy; plasma spray; thermal plasmas